Diminished Alveolar Microvascular Reserves in Type 2 Diabetes Reflect Systemic Microangiopathy - Chance, William W. (American Diabetes Association, 2008)
OBJECTIVE—Alveolar microvascular function is moderately impaired in type 1 diabetes, as manifested by restriction of lung volume and diffusing capacity (DL(CO)). We examined whether similar impairment develops in type 2 diabetes and defined the physiologic sources of impairment as well as the relationships to glycemia and systemic microangiopathy. RESEARCH DESIGN AND METHODS—A cross-sectional study was conducted at a university-affiliated diabetes treatment center and outpatient diabetes clinic, involving 69 nonsmoking type 2 diabetic patients without overt cardiopulmonary disease. Lung volume, pulmonary blood flow (Q̇), DL(CO), membrane diffusing capacity (measured from nitric oxide uptake [DL(NO)]), and pulmonary capillary blood volume (V(C)) were determined at rest and exercise for comparison with those in 45 healthy nonsmokers as well as with normal reference values. RESULTS—In type 2 diabetic patients, peak levels of oxygen uptake, Q̇ and DL(CO), DL(NO), and V(C) at exercise were 10–25% lower compared with those in control subjects. In nonobese patients (BMI <30 kg/m(2)), reductions in DL(CO), DL(NO), and V(C) were fully explained by the lower lung volume and peak Q̇, but these factors did not fully explain the impairment in obese patients (BMI >30 kg/m(2)). The slope of the increase in V(C) with respect to Q̇ was reduced ∼20% in patients regardless of BMI, consistent with impaired alveolar-capillary recruitment. Functional impairment was directly related to A1C level, retinopathy, neuropathy, and microalbuminuria in a sex-specific manner. CONCLUSIONS—Alveolar microvascular reserves are reduced in type 2 diabetes, reflecting restriction of lung volume, alveolar perfusion, and capillary recruitment. This reduction correlates with glycemic control and extrapulmonary microangiopathy and is aggravated by obesity.